Constructing New Stages of Education for Muslim Children: Impacts of the Dissemination of the Iqroâ Method Textbook on Islamic Education in Indonesia and Malaysia - Nakata, Yuki (EDUCARE, 2009)
ABSTRACT: The dissemination of the Iqroâ method textbook through Qurâanic kindergartens and Qurâanic schools in Indonesia has encouraged the publicâs interest in reconsidering teaching methods and the skill of reading and reciting the Qurâan. Moreover, it has provided a chance to reconsider pre-school education for Muslims in Indonesia from the grass-roots level. In Malaysia, both the elementary schools under the Ministry of Education and private schools are also recommended to use Iqroâ method. However, there are several private organizations in Malaysia that have attempted to maintain their originality by using alternatives to Iqroâ, such as Qiraâati and Al-Barqy from Indonesia, and by trying to develop original educational services. This paper tries to explore the dissemination of the Iqroâ method textbook in which it has been revitalized and enriched educational services for Muslims in both Indonesia and Malaysia, by both the government sector and grass-roots efforts across the border.KEY WORDS: the Iqroâ method textbook, Qurâanic kindergartens and Qurâanic schools, and Muslims in both Indonesia and Malaysia.About the Author: Dr. Yuki Nakata is a Lecturer at the Faculty of Law TU (Toyo University), 5-28-20, Hakusan, Bunkyo-ku, Tokyo 112-8606, Japan. She has been conducting the research on Islamic education in Indonesia and Malaysia. For academic purposes, she can be reached at: yuki.nakata@tuba.ocn.ne.jp or nakatayuki9@gmail.comHow to cite this article? Nakata, Yuki. (2009). âConstructing New Stages of Education for Muslim Children: Impacts of the Dissemination of the Iqroâ Method Textbook on Islamic Education in Indonesia and Malaysiaâ in EDUCARE: International Journal for Educational Studies, Vol.2(1) August, pp.25-34. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 23, 2009); Revised (July 25, 2009); and Published (August 17, 2009).